DEMOKRATISASI DAN DEKONSTRUKSI IDEOLOGI GENDER ORDE BARU - Dewi, Kurniawati Hastuti (Pusat Penelitian Politik, 2007)
The collapse ofthe New Order since May 1998 has opened the door for democratization In turn democratization and influence of the international fora on women have facilitated the improvement of Indonesian women s role and position in the public sphere The improvement is highlighted by the deconstruction ofthe New Order gender ideology state ibuism as can be seen from the spread ofthe discourse ofwomen role in the public sphere and the changing orientation of the Government Program from practical gender interest in the New Order to strategic gender interest in the Reform Era However the conceptual and structural improvements face difficulty This is because grass root society keeps negative stereotype on women Thisfact indicates that the efforts to raise women s role and position in the public sphere is not only needed conceptual and structural reform but also cultural reform ofgrass root society s perception on women.